Presenting the model of work and technology curriculum in secondary schools of Fars province - Hamzeh Rahpeyma; Seyedahmad Hashemi; Abbas Gholtash (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to examine the presentation of the curriculum model of work and technology in secondary schools of Fars province. The current research is applicable in terms of purpose, and descriptive-survey in terms of nature and method. The statistical population of this research includes 450 people from all secondary school teachers who teach in the field of work and technology, and 210 people were selected as a sample using Morgan's table. The collection tool in the current research includes a researcher-made questionnaire derived from the qualitative method, which has 4 dimensions: goals (oriented to the educational system, attention to needs assessment, mental ability of the learner, learning time); content (curiosity, meaningful learning, learner characteristics, functional ability); teaching method (problem solving method, work unit (project), small groups, demonstration method); and evaluation (increasing skills, academic progress, increasing job skills, communication skills). The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. Lisrel software was used to fit the conceptual model of the research. The research findings showed that according to the values ​​of standard coefficients and significant t coefficients, it can be said that the goals and content component (β = 0.63) has a significant role in the model, and the teaching and evaluation method component (β = 0.22) has a significant role in the program model of curriculum work and technology in secondary school. All the indicators are very favorable, and the model has a good fit with the data, indicating that there is a linear relationship between the variables. Extended abstract Introduction Since the communication networks of various markets have connected the production and supply of services at the national, regional, and global levels, and considered competitiveness to be the key to entering the global markets, it is obvious that in this global competition, not only countries, but all institutions and people should constantly increase their competitiveness and adaptability (Klofsten et al, 2019). Meanwhile, the attention of many policymakers and political decision makers has been focused on the potential role of entrepreneurs. Entrepreneurship is a process that is known as the key factor of economic growth and development in the modern era, and at the center of international competition are entrepreneurial companies whose competitive edge is focused on organizational flexibility and the strategy of continuous change in processes, products and plans (Tehrani) et al., 2021). To achieve this goal, it seems necessary to cultivate creative ideas and entrepreneurs who can adapt themselves to the new world. The phenomenon of growth and development is serious in the societies that are dynamic and alive with educational and research centers and have a two-way relationship with them and there is movement, innovation and innovation in them. Of course, the real position of education is determined when its role in all-round development such as cultural, social, economic, and political development is also considered (Kalali & Zarkani, 2019). The idea of ​​paying attention to work and technology education has created a lot of enthusiasm in the last few decades, and many effects have been mentioned for this attention, among the most important of which results such as economic growth, job creation, individual growth, increased participation of school in providing services, improving the quality of services and activities can be mentioned (Aslani, 2023). Education of work and technology in schools helps students find an entrepreneurial mindset and expand the knowledge and skills necessary to develop the culture of work and technology in the society. Therefore, the researcher is trying to answer the question: what is the model of work and technology curriculum in secondary schools of Fars province? Theoretical Framework Curriculum Curriculum is actually the proposed educational program that shows how to lead the learner in the direction that is preferred for his growth, and relies on the value system, and the curriculum is a tool to achieve the ideals, realize goals, and fulfill educational objectives. The curriculum deals with the learning outcomes and not only with the predetermined goals but also with the results because the results - in the evaluation position - can include things other than the intended goals and results, and different people may be affected by the set of predetermined measures in different ways (Gholami et al, 2019). Work and technology education in curriculum planning Vocational training can be the main part of the curriculum with a part of the graduation course or a part of other courses. This type of education should be an integral part of all stages of education and training and should be provided through an organized and graded program. (Hashemi et al, 2019). The purpose of teaching work and technology in schools is not only to set up business and work and technology for profit; rather, work and technology is a way of life that is used in all aspects of a person's personal, organizational and social life. Students are the employees, officials, managers and entrepreneurs in the future of the country; if they become familiar with these topics, they will act better at making life and career decisions for themselves, dealing with entrepreneurs and solving their problems. Teacher-oriented education is replaced with Practice-oriented activists of work and technology; so that students become familiar with work and technology through activities and involvement (Fereydun Nezhad, 2023). Zanganeh et al, (2024) investigated the design of the curriculum model of virtual schools in the second period of secondary school in Khaf city. The results showed that school curriculum design includes 6 components: curriculum goals, curriculum content, curriculum evaluation, curriculum learning-teaching flows, curriculum strategies, degree of curriculum suitability; and the results of model fit statistics show that the obtained values for each of the indicators shows a very good fit of the model. Mortazavi Amiri et al, (2023) investigated the design of a dynamic professional learning environment based on an interdisciplinary curriculum with the approach of the effectiveness of knowledge creators in order to provide a model. The results showed that all the components of the dynamic professional learning environment in the field of interdisciplinary lesson planning were identified, and their meaningful dimension was confirmed in the research, and the model of the dynamic professional learning environment was explained based on interdisciplinary lesson planning with an effective approach of knowledge creation by examining the themes, concepts and quantitative and qualitative research. Research methodology The current research is applicable in terms of purpose, and descriptive-survey in terms of nature and method. The statistical population of this research includes 450 people from all secondary school teachers who teach in the field of work and technology, and 210 people were selected as a sample using Morgan's table. The collection tool in the current research includes a researcher-made questionnaire derived from the qualitative method, which has 4 dimensions: goals (oriented to the educational system, attention to needs assessment, mental ability of the learner, learning time); content (curiosity, meaningful learning, learner characteristics, functional ability); teaching method (problem solving method, work unit (project), small groups, demonstration method); and evaluation (increasing skills, academic progress, increasing job skills, communication skills). Research findings The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. Lisrel software was used to fit the conceptual model of the research. The research findings showed that according to the values ​​of standard coefficients and significant t coefficients, it can be said that the goals and content component (β = 0.63) has a significant role in the model, and the teaching and evaluation method component (β = 0.22) has a significant role in the program model of curriculum work and technology in secondary school. All the indicators are very favorable, and the model has a good fit with the data, indicating that there is a linear relationship between the variables. Conclusion The present study was conducted with the aim of investigating the presentation of the curriculum model of work and technology in secondary schools of Fars province. The results of this research are in agreement with the results of Zanganeh et al, (2024), Mortazavi amiri et al, (2023), Mastali et al, (2023), Rajaei (2023), Eisner (2022), Gholamiyan & Farashbandi (2022), Aslan et al, (2021), and Kusumaningtyas et al, (2018). Mortazavi amiri et al, (2023) showed that all the components of the dynamic professional learning environment in the field of interdisciplinary curriculum planning were identified, and the model of the dynamic professional learning environment was explained based on interdisciplinary lesson planning with an effective approach of knowledge creation by examining the themes, concepts and quantitative and qualitative research. According to the present research, the following suggestions are presented: - Teachers ask students to express their experiences in different issues and share them. For this purpose, some parts of the class's time should be allocated to share the experiences and opinions of the students. - Teachers' theoretical and specialized knowledge should be evaluated, and sufficient and complete reports should be provided to school principals and assistants every semester. This should be done by internal evaluators in schools.